A citizen science approach to measuring students' achievement goals. (2019) - Lüftenegger, Marko; Bardach, Lisa; Bergsmann, Evelyn; Schober, Barbara; Spiel, Christiane
Highlights: This study uses a citizen science approach. Students and researchers worked together to develop items assessing achievement goals. Two large studies were conducted (Austria and UK) to test the new scales. Relations to external linkages of achievement goals were also investigated. Abstract: The concept of citizen science in scientific research brings researchers and laypersons together to work on research projects. Using an achievement goal theory framework, the present study employs a citizen science approach in which researchers and students collaboratively developed items assessing students' achievement goals (mastery-approach, normative and appearance performance-approach, normative and appearance performance-avoidance goals). The newly developed scales were tested in two large studies carried out in Austria and the United Kingdom. All scales exhibited good psychometric properties (validity, reliability). Measurement invariance across the investigated subjects (mathematics and German in Austria and mathematics and English in the United Kingdom) and the two countries was established. Moreover, we investigated relations to implicit theories, self-efficacy, reference norms, and adaptive reactions to errors.